2017
DOI: 10.4172/pharmaceutical-sciences.1000271
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Gallate, a Green Tea Polyphenol Inhibits Mycobacterium smegmatis: In silico and In vitro Studies

Abstract: Narayanan and Ramesh: Epigallocatechin Gallate Inhibits M. smegmatisPresence of multidrug resistant strains makes treatment of tuberculosis difficult. Conventional frontline antituberculosis therapy has high incidence of treatment failure due to non-adherence and severe side effects, and therefore warrants alternative approaches using safe, natural compounds. (-) Epigallocatechin gallate, a green tea catechin with significant antimicrobial properties, and its derivatives have been studied for their inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Aiming to understand this differential affinity, a future perspective of our group will be to gain insights, through molecular docking analyses, in the potential binding modes of G28 and monoesters to their target FASN catalytic domains. These domains are probably the same as those targeted by EGCG, the NADPH-dependent domains ketoreductase (KR) [ 35 ] and enoyl reductase (ER) [ 36 , 37 , 38 , 39 ], which participate in the saturation of the growing fatty acid chain [ 40 ]. Interestingly, EGCG has been shown to compete with NADPH/NADH for binding to KR and ER [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming to understand this differential affinity, a future perspective of our group will be to gain insights, through molecular docking analyses, in the potential binding modes of G28 and monoesters to their target FASN catalytic domains. These domains are probably the same as those targeted by EGCG, the NADPH-dependent domains ketoreductase (KR) [ 35 ] and enoyl reductase (ER) [ 36 , 37 , 38 , 39 ], which participate in the saturation of the growing fatty acid chain [ 40 ]. Interestingly, EGCG has been shown to compete with NADPH/NADH for binding to KR and ER [ 35 , 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These domains are probably the same as those targeted by EGCG, the NADPH-dependent domains ketoreductase (KR) [ 35 ] and enoyl reductase (ER) [ 36 , 37 , 38 , 39 ], which participate in the saturation of the growing fatty acid chain [ 40 ]. Interestingly, EGCG has been shown to compete with NADPH/NADH for binding to KR and ER [ 35 , 36 , 37 , 38 , 39 ]. Since both NADPH/NADH (FASN) and GTP (FtsZ) are nucleotides, it is worth noting that, in the FtsZ study, the galloyl groups and the naphthalene scaffold of G28 were predicted to replace the interactions by the phosphates and the nucleobase of the nucleotide, respectively [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epigallocatechin gallate showed a cytotoxicity of 18.6% at eight µg/ml, while the two derivatives did not show any toxicity. The non-mutagenic epigallocatechin gallate inhibits M. smegmatis growth and warrants further investigation as an adjunct therapy for pathogenic mycobacteria 86 .…”
Section: Role Of Polyphenols In Respiratory Diseasesmentioning
confidence: 99%
“…In a very recent study, GTP epigallocatechin-3-gallate was demonstrated to inhibit InhA, the enoyl-ACP reductase of mycobacterium. This has prompted us to screen in silico a set of GTPs against various pivotal targets of mycobacterium including InhA [6,7]. For the best-docked top three hits with higher docking scores, we listed down their drug-likeness assessment, and ADMET (absorption, distribution, metabolism, excretion, toxicity) properties.…”
Section: Introductionmentioning
confidence: 99%